CHARACTERISTICS OF METRIC PARAMETERS OF THE ILEUM WALL IN RATS UNDER LONG-TERM COMPLEX INFLUENCE OF CHEMICAL FOOD ADDITIVES - Bilash, S.M.; Oliinichenko, Ya.O.; Pronina, O.M.; Koptev, M.M.; Pirog-Zakaznikova, A.V.; Donchenko, S.V.; Mamai, O.V. (World of Medicine and Biology, 2024)
It has been experimentally proven that chemical food additives can cause changes in the morphological structure of various internal organs, including the digestive system. To date, data on the complex effects of these substances on the ileum are rather limited. It justified the aim of the study, which was to investigate changes in the intestinal wall after long-term administration of a complex of chemical food additives, including monosodium glutamate, sodium nitrite and ponceau 4R. In this study, using histological and morphometric methods of research, we determined the dynamic changes in the overall average wall thickness and its separate layers. It was found that the ileum of rats of both the control group (receiving saline) and the experimental groups (receiving a complex of chemical food substances for 1, 4, 8, 12, 16, and 20 weeks) is represented by serosa, muscular layer, submucosa and mucosa. It has been established that changes occur for up to 8 weeks due to hyperhydration of connective tissue and pericellular oedema of the structural components of all layers. However, starting from week 12, there are signs of irreversible changes that progress to week 20 and manifest as dystrophic changes with subsequent atrophy of the ileal wall, confirmed by a decrease in all indicators. Thus, with their prolonged administration, chemical food additives disrupt the protective and adaptive mechanisms of the ileum.
Keywords: ileum; intestinal wall; food additives; morphometric analysis; rats; mucosa; serosa; lymphocytes